2000
DOI: 10.1111/j.1540-8159.2000.tb00834.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Results of a Bipolar Active Fixation Lead for Atrial Application: An Interim Analysis

Abstract: Adequate atrial lead performance consists of stable sensing and pacing properties. To evaluate whether the CPI 4269 bipolar lead, covered with mannitol (Sweet Tip), in the atrial position encounters these properties, we performed a prospective study of this lead. After complete dissolution of the mannitol helix, mapping of the atrium to obtain the highest electrogram and lowest threshold was followed by screw-in into the endocardium. Intraoperative measurements were performed and long-term follow-up was schedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Despite this, there remains a reluctance to routinely use active‐fixation leads in the ventricle mainly because of concerns regarding both acutely and chronically high stimulation thresholds which have not been confirmed on limited studies 4,17 . There are also concerns regarding electrode perforation particularly with the atrial lead, 18,19 although the chronic use of active‐fixation leads in the atrium is well established 2,20,21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, there remains a reluctance to routinely use active‐fixation leads in the ventricle mainly because of concerns regarding both acutely and chronically high stimulation thresholds which have not been confirmed on limited studies 4,17 . There are also concerns regarding electrode perforation particularly with the atrial lead, 18,19 although the chronic use of active‐fixation leads in the atrium is well established 2,20,21 …”
Section: Discussionmentioning
confidence: 99%
“…4,17 There are also concerns regarding electrode perforation particularly with the atrial lead, 18,19 although the chronic use of active-fixation leads in the atrium is well established. 2,20,21 Previous studies examining the performance of active-fixation leads have not reported on acute changes in stimulation thresholds during the op-erative period. 2,4,7,22,23 The results of lead testing during implantation are critically important in determining whether lead repositioning is required.…”
Section: Main Observationsmentioning
confidence: 99%
“…The problem of atrial lead stability, which was a matter of concern in the early days of dual‐chamber pacing, has been partially solved in recent years by the use of the screw‐in mechanism, both in J‐shaped and straight leads. Encouraging data are available on the safety and performances of screw‐in atrial systems, both with an exposed mannitol‐coated helix and an extendable/retractable helix 1,3,4 . Pre‐J‐shaped leads have been seen to offer an advantage over straight leads in terms of their lower rate of acute dislocations 5 …”
Section: Introductionmentioning
confidence: 99%
“…Encouraging data are available on the safety and performances of screw-in atrial systems, both with an exposed mannitol-coated helix and an extendable/retractable helix. 1,3,4 Pre-J-shaped leads have been seen to offer an advantage over straight leads in terms of their lower rate of acute dislocations. 5 Recently, a randomized comparative study was carried out on J-shaped leads with and without active-fixation mechanisms.…”
Section: Introductionmentioning
confidence: 99%